Silicon and nano-silicon in environmental stress management and crop quality improvement : progress and prospects - Etesami, Hassan (Academic Press, 2022)
Silicon and Nano-silicon in Environmental Stress Management and Crop Quality Improvement: Progress and Prospects provides a comprehensive overview of the latest understanding of the physiological, biochemical and molecular basis of silicon- and nano-silicon-mediated environmental stress tolerance and crop quality improvements in plants. The book not only covers silicon-induced biotic and abiotic stress tolerance in crops but is also the first to include nano-silicon-mediated approaches to environmental stress tolerance in crops. As nanotechnology has emerged as a prominent tool for enhancing agricultural productivity, and with the production and applications of nanoparticles (NPs) greatly increasing in many industries, this book is a welcomed resource.